Acute toxicity of potassium permanganate to fingerlings of the African catfish, Clarias gariepinus (Burchell, 1822) - Kori-Siakpere; Ovie (Advances in Aquaculture and Fisheries Management, 2020)
Laboratory static bioassays were conducted to determine the 96-h LC50 and the lethal levels of concentrations of the aquaculture therapeutant, potassium permanganate (KMnO4) on fingerlings (mean weight, 6.24 ± 0.15 g and mean length, 4.25 ± 0.07 cm) of the African catfish, Clarias gariepinus. A total number of one hundred and eighty (180) fingerlings of mixed sex and brood stock were used for the toxicity bioassay. The 96-h median lethal concentration (LC50) value obtained for treatment of the fingerlings of the catfish C. gariepinus with potassium permanganate was 3.02 mg/L KMnO4 with lower and upper 95% confidence limits of 0.40 and 3.73 mg/L KMnO4, respectively. There was very strong and positive correlation between the variables (r = 0.96) with 93% (r2 ) association. Toxicity curve revealed 11.20 mg/L KMnO4 at 8.20 h as the threshold value for the 96 h assay of potassium permanganate on fingerlings of C. gariepinus. The 96 h LT50 for 10, 8 and 6 mg/L KMnO4 to the test fish were also determined to be 10.40, 11.30 and 17.80 h, respectively. Varying behavioural patterns were observed in the fish, which included erratic swimming, loss of reflexes, total loss of equilibrium, paleness of skin and gasping for air. The value of water quality parameters monitored during the exposure period did not differ significantly (P>0.05) within the various concentrations of the therapeutant (KMnO4) as well as with the control. However, pH and total alkalinity tended to increase with increasing concentration of the toxicant.